Standar Pelayanan dan Barang Dagangan Anggota Koperasi di Koperasi Pedagang Pusat Perbelanjaan Depok (KPPD) - Setyadi, Cecep; Syarif Hidayat, ahmad; Octavia, Santi; Supriani, Yayan; Masmualim, Masmualim; elinda safitri, Nur; Nabila, Khaylila; Damara Saputra, Doni; Yatno, Yatno; Rahmawati, Alifia (STIE MBI, 2025)
This study aims to understand how service standards and merchandise management are implemented by members of the Koperasi Pedagang Pusat Perbelanjaan Depok (KPPD). This cooperative plays an important role in supporting the economic activities of traders in the shopping center, particularly in providing merchandise and improving service quality to customers. Using a descriptive qualitative approach, data were collected through direct observation, interviews with cooperative members, and documentation of cooperative activities. The findings show that most members have applied good service standards, such as friendliness, punctuality, and cleanliness of their business premises. However, there are still several challenges, such as irregular inventory management and a lack of regular training provided by the cooperative. In terms of merchandise, most members offer products that meet consumer needs, although not all have adopted neat and systematic record-keeping practices. This study recommends that the cooperative take a more active role in providing training and conducting regular supervision to maintain consistent service standards and merchandise quality. By doing so, KPPD can continue to grow as a professional and trustworthy collective economic institution for its members.